Clinical efficacy of a stent-in-stent procedure for stent fracture in a narrowing anastomosis of femoral-popliteal bypass represented repetitive acute limb ischemia. Issue 1 (January 2018) - Nojima, Yuhei; Nanto, Shinsuke; Adachi, Hidenori; Ihara, Madoka; Kurimoto, Tetsuya
Abstract: A 72-year-old male with sudden onset pain and coldness in his left lower limb was referred to our hospital. An emergency angiography of the lower limbs demonstrated the cause of acute limb ischemia as a subsequent acute thromboembolism at the site of a narrowing anastomosis of femoral-popliteal bypass (FPB). In particular, the site of the narrowing anastomosis had already been fixed using a nitinol stent 4 years previously. We confirmed that the severe stent fracture resulted from misalignment. After local lysis therapy, we decided to deploy another nitinol stent to in-stent restenosis (ISR) lesion of the stent fracture. Final angiography confirmed full patency in FPB without flow delay. Additionally, to maintain the patency of arterial flow, we prescribed aspirin and warfarin. After 2 years of operation, his follow-up ankle-brachial pressure index on the left side remained 0.86 and no ischemic leg pain was observed to date. Stent-in-stent procedure using another nitinol stent for ISR treatment for the narrowing anastomosis in FPB indicated feasible and effective results. <Learning objective: Endovascular intervention for acute limb ischemia (ALI) is one of the most challenging cases. Physicians often come up against a problem as no-flow phenomenon after revascularization. Local lysis therapy has established its own position in ALI treatment. However, the effectiveness of various interventional treatments for ALI has not been clarified. This report highlights the potential of a combination of local lysis and intervention in achieving good outcomes in represented repetitive ALI.>